Znaczenie recepcji dorobku Bronisława Malinowskiego dla rozważań etyki gospodarczej nad kryzysem finansowo-gospodarczym - Szulczewski, Grzegorz (Annales. Etyka w Życiu Gospodarczym, 2011)
The paper presents two theories from the area of cultural anthropology. The first is B. Malinowski, who criticized economism andmoralism. I present further stages of this criticism, with special importance placed on the concept of homo oeconomicus. Malinowski alsoshowed how moral norms are implemented in primitive cultures by means of magic, cults, customs and rituals and rites. Another importantsection is devoted to Malinowski’s analysis of how cultural institutions were important for stable functioning of primitive communities.They sheltered those communities form crisis of the kind that we experience today. The second theory is economical ethics of K. Hofman,one of the newest achievements of German business ethics. So works of cultural anthropology are worth being read again.